2021
DOI: 10.1002/pbc.29545
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric severe factor XI deficiency: A multicenter study

Abstract: Background Factor XI (FXI) deficiency is a rare autosomal recessive bleeding disorder. Only scarce publications address its clinical features in children. The increased prevalence of FXI deficiency in Israel enabled data collection for this large multicenter cohort study. Objective Some hemostatic challenges may be unique or more common in children, such as bleeding in the neonatal period or trauma‐related injury. The current study was designed to explore the potential impact of these differences in children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…23 A large multicenter cohort study reported that in children with severe FXI deficiency and ICH, plasma infusion is the mainstay of therapy, and recombinant FVII may be considered for patients with levels <1% due to risk of FXI inhibitor development. 22,23 FXI levels >30% are considered hemostatic, especially in patients undergoing surgery. 23 While the development of CSVT in children with inherited BDs is uncommon, the management of such thrombi are based on adult experiences, indicating that short-duration anticoagulation with concurrent factor prophylaxis may be feasible with close monitoring of factor levels and intracranial imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 A large multicenter cohort study reported that in children with severe FXI deficiency and ICH, plasma infusion is the mainstay of therapy, and recombinant FVII may be considered for patients with levels <1% due to risk of FXI inhibitor development. 22,23 FXI levels >30% are considered hemostatic, especially in patients undergoing surgery. 23 While the development of CSVT in children with inherited BDs is uncommon, the management of such thrombi are based on adult experiences, indicating that short-duration anticoagulation with concurrent factor prophylaxis may be feasible with close monitoring of factor levels and intracranial imaging.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 FXI levels >30% are considered hemostatic, especially in patients undergoing surgery. 23 While the development of CSVT in children with inherited BDs is uncommon, the management of such thrombi are based on adult experiences, indicating that short-duration anticoagulation with concurrent factor prophylaxis may be feasible with close monitoring of factor levels and intracranial imaging. 5,24 Pediatric studies in CSVT following trauma with ICH indicate that anticoagulation therapy may be safe with close monitoring and without worsening of ICH, although as mentioned in pediatric CHEST guidelines, withholding anticoagulation therapy with watchful waiting and imaging surveillance is an appropriate alternative in certain cases, as thrombi can resolve spontaneously due to physiologic processes including fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation